Nonverbal communication - Burgoon, Judee K.; Manusov, Valerie Lynn; Guerrero, Laura K. (New York, NY Routledge, 2022)
"The newly revised edition of this groundbreaking textbook provides a comprehensive overview of the theory, research, and applications of nonverbal communication. Authored by three of the foremost scholars in the field and drawing on multidisciplinary research from communication studies, psychology, linguistics, and family studies, Nonverbal Communication speaks to today's students with modern examples that illustrate nonverbal communication in their lived experiences. It emphasizes nonverbal codes as well as the functions they perform to help students see how nonverbal cues work with one another and with the verbal system through which we create and understand messages. Chapters cover the social and biological foundations of nonverbal communication as well as the expression of emotions, interpersonal conversation, deception, power, and influence. This edition includes new content on "Influencing Others", as well as a revised chapter on "Displaying Identities, Managing Images, and Forming Impressions" that combines identity, first impressions and impression management. Nonverbal Communication serves as a core textbook for undergraduate and graduate courses in communication and psychology."--Provided by publisher.
Includes bibliographical references and index.
Keywords: Body language; Nonverbal communication